2021
DOI: 10.1073/pnas.2010357118
|View full text |Cite
|
Sign up to set email alerts
|

The DUF1013 protein TrcR tracks with RNA polymerase to control the bacterial cell cycle and protect against antibiotics

Abstract: How DNA-dependent RNA polymerase (RNAP) acts on bacterial cell cycle progression during transcription elongation is poorly investigated. A forward genetic selection for Caulobacter crescentus cell cycle mutants unearthed the uncharacterized DUF1013 protein (TrcR, transcriptional cell cycle regulator). TrcR promotes the accumulation of the essential cell cycle transcriptional activator CtrA in late S-phase but also affects transcription at a global level to protect cells from the quinolone antibiotic nalidixic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(15 citation statements)
references
References 61 publications
(92 reference statements)
0
15
0
Order By: Relevance
“…We discovered that TipR significantly binds 4 chromosomal targets in vivo. Importantly, TipR occupancy of these sites is reduced by ≈500% after exposing cells to NAL (for 30 minutes; Figs 1F and S2A and S3 Data ), indicating that NAL antagonizes repression of P acrA and P tipR by TipR in vivo, allowing recruitment of RNAP (and TrcR [ 10 ]). The coordinated induction of AcrAB-NodT and TipR by NAL points towards a homeostatic control mechanism in which the adaptive and transient resistance to β-lactam antibiotics is conferred by induction of AcrAB-NodT, followed by TipR synthesis to reestablish the repressed ground state once the inducers have been expelled by AcrAB-NodT.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We discovered that TipR significantly binds 4 chromosomal targets in vivo. Importantly, TipR occupancy of these sites is reduced by ≈500% after exposing cells to NAL (for 30 minutes; Figs 1F and S2A and S3 Data ), indicating that NAL antagonizes repression of P acrA and P tipR by TipR in vivo, allowing recruitment of RNAP (and TrcR [ 10 ]). The coordinated induction of AcrAB-NodT and TipR by NAL points towards a homeostatic control mechanism in which the adaptive and transient resistance to β-lactam antibiotics is conferred by induction of AcrAB-NodT, followed by TipR synthesis to reestablish the repressed ground state once the inducers have been expelled by AcrAB-NodT.…”
Section: Resultsmentioning
confidence: 99%
“…To search for determinants conferring β-lactam resistance in cells lacking MBL, we conducted a transposon (Tn) mutagenesis of Δbla mutant cells, delivering the Tn by intergeneric conjugation from an E. coli donor. Initially, we counterselected the donor on plates containing NAL (20 μg/mL, NAL 20 ), but we unexpectedly observed that Δbla cells grew on PIR 40 or CEF 10 plates supplemented with NAL 20 . NAL is not known to affect β-lactam resistance directly, as it targets the A subunit of DNA gyrase (GyrA) in susceptible bacteria.…”
Section: Nal-induced Adaptive Resistance To β-Lactams Requires Acrab-...mentioning
confidence: 99%
See 3 more Smart Citations